Picrosirius red staining assessment of collagen after dermal roller application: A minimally invasive percutaneous collagen induction therapy - Fatma El-Zahraa Sa; Reham Ezz El-Dawela; Mohammad Abel Kerim (Wolters Kluwer Medknow Publications, 2014)
Background: Percutaneous collagen induction (PCI) through dermal roller breaks old collagen strands, promotes removal of damaged collagen and induces more collagen formation. Collagen fibers can be assessed by traditional stains or by polarized light assessment of Picrosirius red stain. Objective: The purpose of the current study is the clinical and histopathological evaluation of percutaneous collagen formation in atrophic acne scars after dermal roller application. Patients and Methods: Total study duration was 26 weeks in which 12 patients received seven sessions of PCI at 3-weeks interval, 3 mm punch biopsy specimens of scars were obtained before and after treatment (at 18 and 26 weeks). Microscopic examination of pre and post operative biopsies were done, using routine stains and Picrosirius red stain. Results: PCI induced notable improvement in the appearance of acne scars with significant reduction in the score from 123.3 ± 24.5 to 74.16 ± 16.49 (P = 0.00) after 26 weeks. Polarized light assessment of Picrosirius red stain clarified the gradual replacement of old thick orange-red birefringent collagen fibers by newly synthesized thin green-yellow birefringent ones postoperatively. Conclusion: Skin needling is a simple and minimally invasive procedure. The polarized light assessment of Picrosirius red stain clarified the change of the optical properties of collagen fibers according to the maturation process.